Burnout and presenteeism among healthcare workers in Nigeria: Implications for patient care, occupational health and workforce productivity - Arinze D.G. Nwosu; Edmund Ossai; Okechukwu Onwuasoigwe; Maureen Ezeigweneme; Jude Okpamen (SAGE Publishing, 2021)
Background: Burnout and presenteeism are two emerging occupational health challenges which share same locus among healthcare workers, and the trend is rising. We aim to define the magnitude of burnout and presenteeism among frontline members of the health workforce and explore any correlation between the two in order to provide empirical data from our socioeconomic and geographical background.  Design and Methods: We used self-administered questionnaire to conduct a cross-sectional study among the physicians and nurses in a regional trauma centre in Enugu, Eastern Nigeria; with the respondents selected by stratified random sampling. The Oldenburg burnout inventory and Stanford presenteeism scale were used to measure burnout and presenteeism respectively, while the 2-item patient-health questionnaire (PHQ-2) was used to screen for depression. The level of statistical significance was determined by a p value of <0.05. Results: Among the healthcare workers surveyed (n=155); 34 (21.9%) were physicians, while 121 (78.1%) were nurses. Burnout prevalence was 69%. Burnout was associated with self-rated health status and length of years in professional service but not the occupation or depression screen status of the worker. Sixty-two healthcare workers (40%) screened positive for depression. A positive screen for depression was the only factor that had significant association with lower presenteeism scores (p=0.002). The mean presenteeism scores had strong negative correlation with both the exhaustion (p<0.001) and disengagement (p<0.001) domains of burnout. Conclusion: Burnout is high among the healthcare workers and correlates with presenteeism scores. The mental health of the workforce greatly impaired their productivity.